Pancreatic cystic lesions: An 11 years (2010–2020) of experience at Usmanu Danfodiyo University teaching hospital, Sokoto - Bello M Bashir; Stephen P Agbo; Muhammad Muktar Umar; Ibrahim Umar Abubakar; Hamza Ibrahim Sani; Mikailu Abdullahi; Faruk O Emetuma (Nigerian Journal of Medicine, 2022)
Background: Pancreatic cystic lesions are heterogeneous lesions that could be benign, borderline, or malignant. Neoplastic cystic lesions/tumours are rare tumours of the exocrine pancreas; difficult to diagnose preoperatively, and they account for 2%–10% of pancreatic tumours. Pancreatic pseudocyst is the most typical benign cystic pancreatic lesion arising from pancreatic ductal inflammation or ductal disruption. Both benign and malignant cystic pancreatic lesions are amenable to surgical treatments, with a good prognosis. Aim: The aim is to present our 11yrs of experience in the management of pancreatic cystic lesions. Materials and Methods: We conducted a retrospective review of pancreatic cystic lesions managed at the General Surgery Unit of Usmanu Danfodiyo University, Sokoto, Nigeria, from 2010 to 2020. A retrospective review of the case notes of patients was done with an emphasis on biodata, presentation, investigations treatment offered, complications, and follow-up were analysed using the Statistical Package for the Social Science (SPSS) version 22, Inc. (Chicago II, USA). Results: We managed 28 patients over 11 years. Three patients had pancreatic cystic tumours, whereas 25 patients had pancreatic pseudocysts. The age ranges of the patient with pancreatic cystic tumours are 29–50 years with a male-to-female ratio of 2:1. All the patients had tumour excision with histology revealing two pseudopapillary tumours of the pancreas and one serous cystadenoma. The age range of patients with pseudocyst is 27–42 years with a male-to-female ratio of 1:3.1, and most of the patient had internal drainage. Conclusion: Pancreatic cystic tumours are uncommon pancreatic neoplasms that are amenable to surgical interventions with a good prognosis. Pancreatic pseudocyst was seen mainly in females within the young age group. Both benign and neoplastic pancreatic cystic lesions are amenable to surgical intervention with a good prognosis.